Current Knowledge on Mechanisms Preventing Photosynthesis Redox Imbalance in Plants - María-Cruz González; Francisco Javier Cejudo; Mariam Sahrawy; Antonio Jesús Serrato (MDPI AG, 2021)
Photosynthesis includes a set of redox reactions that are the source of reducing power and energy for the assimilation of inorganic carbon, nitrogen and sulphur, thus generating organic compounds, and oxygen, which supports life on Earth. As sessile organisms, plants have to face continuous changes in environmental conditions and need to adjust the photosynthetic electron transport to prevent the accumulation of damaging oxygen by-products. The balance between photosynthetic cyclic and linear electron flows allows for the maintenance of a proper NADPH/ATP ratio that is adapted to the plant's needs. In addition, different mechanisms to dissipate excess energy operate in plants to protect and optimise photosynthesis under adverse conditions. Recent reports show an important role of redox-based dithiol-disulphide interchanges, mediated both by classical and atypical chloroplast thioredoxins (TRXs), in the control of these photoprotective mechanisms. Moreover, membrane-anchored TRX-like proteins, such as HCF164, which transfer electrons from stromal TRXs to the thylakoid lumen, play a key role in the regulation of lumenal targets depending on the stromal redox poise. Interestingly, not all photoprotective players were reported to be under the control of TRXs. In this review, we discuss recent findings regarding the mechanisms that allow an appropriate electron flux to avoid the detrimental consequences of photosynthesis redox imbalances.